Gender differences in bicuspid aortic valve Sievers types, valvulopathy, aortopathy, and outcome of aortic valve replacement. Issue 8 (29th June 2022) - Li, Yijia; Chen, Xiongwen; Qi, Yue; Qu, Yichen; Kumar, Akshay; Dong, Songbo; Yang, Yan; Zhao, Qiong
Abstract: Background: The gender difference of the bicuspid aortic valve (BAV) is not well understood. Objectives: We evaluated the impact of gender on the Sievers types, valvulopathy, aortopathy, and outcomes of aortic valve replacement (AVR) of BAV patients in a cohort of Chinese patients. Methods: Among 992 BAV patients without aortic dissection nor congenital heart disease, 658 underwent AVR. The demography, Sievers types, valvulopathy, aortopathy, and outcomes of AVR were compared between genders. Results: Aortic regurgitation (AR ≥ 2+) (39.0% vs. 12.8%, p < .001), aortic root dilation only (3.8% vs. .8%, p = .014), and diffuse dilation (25.3% vs. 4.3%, p < .001) were more common in men, while moderate to severe aortic stenosis (AS) (21.3% vs. 45.7%, p < .001) and ascending dilation only (46.2% vs. 61.2%, p < .001) were more common in women. Men were more prone to develop preoperative AR ≥ 2+ (OR = 5.15, p < .001), moderate to severe AS + AR ≥ 2 + (OR = 2.95, p = .001), and Diffuse aortic dilation (OR = 3.91, p < .001). Sievers types did not have a significant effect on valvular dysfunction. Gender didn't predict early adverse events after AVR ( n = 90) (HR = 1.21, p = .44), but male gender predicted a left ventricular ejection fraction <50% after AVR (OR = 3.07, p = .03). Conclusions: In this BAV series of Chinese patients, gender didn't differ significantly in Sievers types of BAV but showed significant differences in valvulopathy, aortopathy, and LV function after AVR. In addition, the male patients developed more severe conditions at a younger age.